2013
DOI: 10.5194/amt-6-35-2013
|View full text |Cite
|
Sign up to set email alerts
|

Observation of volcanic ash from Puyehue–Cordón Caulle with IASI

Abstract: Abstract. On 4 June 2011 an eruption of the Chilean volcano complex Puyehue-Cordón Caulle injected large amounts of volcanic ash into the atmosphere and affected local life as well as hemisphere-wide air traffic. Observations of the Infrared Atmospheric Sounding Interferometer (IASI) flown on board of the MetOp satellite have been exploited to analyze the evolution of the ash plume around the Southern Hemisphere. A novel singular vector-based retrieval methodology, originally developed for observation of deser… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 49 publications
6
64
0
1
Order By: Relevance
“…The calculations also showed that 43 % of all air parcels reached the vicinity of Lauder, and the volcanic aerosol plume from the PCCVC eruption remained near the tropopause level in the mid-latitudes of the Southern Hemisphere. These results agree with the findings of Klüser et al (2013), who used backward trajectory calculations and observations of the Infrared Atmospheric Sounding Interferometer (IASI) on board the MetOp satellite to determine the evolution of the ash plume around the Southern Hemisphere.…”
Section: Comparisons Of Aerosol Vertical Profiles Before and After Thsupporting
confidence: 82%
See 2 more Smart Citations
“…The calculations also showed that 43 % of all air parcels reached the vicinity of Lauder, and the volcanic aerosol plume from the PCCVC eruption remained near the tropopause level in the mid-latitudes of the Southern Hemisphere. These results agree with the findings of Klüser et al (2013), who used backward trajectory calculations and observations of the Infrared Atmospheric Sounding Interferometer (IASI) on board the MetOp satellite to determine the evolution of the ash plume around the Southern Hemisphere.…”
Section: Comparisons Of Aerosol Vertical Profiles Before and After Thsupporting
confidence: 82%
“…In each ratio, we observed three peaks above the tropopause height in the analysis period: on 11 June, 23 June, and 4 July. This result suggests that the volcanic aerosol plume circled the Southern Hemisphere three times, a finding that was confirmed by using IASI, Ozone Monitoring Instrument (OMI), and Moderate Resolution Imaging Spectroradiometer (MODIS) satellite data (not shown) (Klüser et al, 2013). To examine the three peaks of the aerosol vertical profiles in greater detail, we calculated the particle depolarization ratio δ p , to estimate the non-sphericity of the particles:…”
Section: Vertical Profiles Of the Backscattering Ratio And The Depolamentioning
confidence: 99%
See 1 more Smart Citation
“…The eruption plume was observed by several nadir sounders measuring at ultraviolet (NASA Earth Observatory, 2013; NASA OMI, 2013), visible (NASA MODIS, 2013) and infrared wavelengths (Klüser et al, 2013). The nadir sounders traced the circulation of the volcanic ash around the Southern Hemisphere for more than 10 days.…”
Section: Volcanic Ash Detection Threshold Derived From Mipas Observatmentioning
confidence: 99%
“…Several different approaches have been applied to the infrared spectra of different volcanic plumes, including methods based upon optimal estimation (Clarisse et al, 2010;Francis et al, L. J. Ventress et al: Retrieval of ash properties from IASI measurements 2012; Pavolonis et al, 2013a), singular value decomposition (Klüser et al, 2013), and a split window (Wen and Rose, 1994a;Prata and Grant, 2001). These methods have been applied to both hyperspectral and broadband satellite instruments, each of which has advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%